THE INFLUENCE OF CORPORATE SUSTAINABILITY ON TAX DISTRIBUTION AND DIVIDEND DISTRIBUTION - Siagian, Valentine; Sinaga, Nensy Dwi Putri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
This study investigates the impact of corporate sustainability on effective tax rates and dividend payout ratios among companies listed in the LQ45 index over the period from 2018 to 2022. Corporate sustainability is increasingly recognized as a crucial aspect of business strategy, influencing financial structures and shareholder value distribution. Utilizing a panel data analysis taken from Bloomberg, we explore how sustainability growth rate affect their tax strategies and dividend policies. Our findings reveal a nuanced interaction between corporate sustainability and fiscal obligations. Specifically, the study indicates that higher levels of corporate sustainability correlate with a lower effective tax rate; however, this relationship is statistically insignificant. This suggests that while sustainable practices may influence tax-related decisions, other factors such as changes in tax legislation, profitability, and tax planning strategies might play more pivotal roles in determining the effective tax rate. Conversely, the impact of corporate sustainability on dividend payout ratios is both negative and statistically significant. Companies with robust sustainability practices tend to reinvest a greater portion of their earnings back into the business to support sustainable growth and long-term value creation, leading to lower dividend distributions. This finding highlights the prioritization of capital retention over immediate shareholder returns among sustainably focused firms in the LQ45 index. This research contributes to the understanding of how sustainability initiatives intersect with financial policies within Indonesian listed companies. The insights provided could help investors and policymakers better understand the financial implications of sustainability growth rate, particularly in emerging markets where such practices are gaining momentum. The results also suggest areas for further research, particularly in exploring the indirect pathways through which sustainability might influence corporate financial policies.